Control químico de malezas en el cultivo de maíz (Zea mays L.), en sistema de siembra directa, en el Rcto. Los Ángeles, Cantón Ventanas”. - López Plaza, Freddy Eloy (2020)
This document was made with the purpose of determining the importance of carrying out chemical weed control in the cultivation of corn planted by means of a direct sowing system, where it is essential to carry out an effective weed control due to the fact that by not practicing conventional tillage the Soil has coverage, which promotes that weeds develop more easily. For the development of this practical document, surveys were conducted consisting of seven closed questions, which were tabulated using the Microsoft Excel program and diagrammed in bar graphs. The interview was conducted with fifteen Rcto producers. Los Angeles, Canton Windows. Additional information was collected from publications of books, magazines, scientific articles, congresses, papers, newspapers, web pages; what was submitted to the technique of analysis, synthesis and paraphrase on the chemical control of weeds in the cultivation of corn, by means of a direct sowing system. According to what was developed, it was determined that most of the producers carry out the sowing of the corn crop through conventional tillage, not relying on the benefits obtained from zero tillage by taking advantage of the remains of plant materials that the soil has, which promotes erosion and prevents degradation of the same, accumulating organic matter, which provides nutrients and it is necessary that weed control is carried out with the doses and time of application of the products according to the development of the corn crop and weeds present , because if there is no adequate control, they compete with the crop for water, light and nutrients which significantly affects the yield.